A randomized controlled trial comparing everting sutures with everting sutures and a lateral tarsal strip for involutional entropion - Scheepers, M.A.; Singh, R.; Ng, J.; Zuercher, D.; Gibson, A.; Bunce, C.; Fong, K.; Michaelides, M.; Olver, J. (Elsevier, 2010)
Objective: To determine whether there is a statistically significant difference in the surgical outcome of everting sutures (ES) alone versus everting sutures with a lateral tarsal strip (ES + LTS) in the treatment of involutional entropion. Design: Prospective randomized comparative trial. Participants: Sixty-three patients with primary involutional lower eyelid entropion were enrolled in the study. The age range was 54 to 94 years, with a mean age of 77 years. Baseline characteristics of the comparative groups were similar. Methods: Patients requiring primary surgical repair for involutional entropion were selected, and those providing informed consent were randomized for surgery. Thirty-six patients were randomized to ES alone, and 27 patients were randomized to ES + LTS. Patients were evaluated at 3 weeks and 6, 12, and 18 months postoperatively. Main Outcome Measures: Successful surgery was defined as a normal eyelid position at rest and inability to induce entropion on tetracaine provocation testing at or before the 18-month follow-up visit. Results: Eight patients were lost to follow-up (7 had ES alone). Of the 55 patients with complete follow-up data, there were 6 failed procedures in the patients who underwent ES alone and no failed procedures in the patients who underwent ES + LTS (P = 0.02). Conclusions: These data provide strong evidence that success rates at 18 months are higher in patients treated with ES + LTS procedure compared with ES alone. Financial Disclosure(s): The authors have no proprietary or commercial interest in any materials discussed in this article. Ophthalmology 2010; 117: 352-355 (C) 2010 by the American Academy of Ophthalmology.